Evaluation of student assessment practices in a medical college - Elfaki, Omer A.; Alamri, Abdulaziz A. (International Journal of Research in Medical Sciences, 2017)
Background: The importance of students’ assessment and its role in driving students learning are well recognized. Guidelines for good assessment practice have been developed. The GMC issued important recommendations related to assessment of students’ performance to be followed by medical schools in UK. The Liaison Committee on Medical Education (LCME) developed standards emphasizing the importance of documenting students’ performance. The utility concept of an assessment tool had been proposed by Van der Vleuten stating a number of weighted criteria. Assessment of clinical competence was proposed to be well covered by the model of Miller. No single method of assessment can be recommended to be appropriate for all assessment purposes and all domains of competence. Therefore, multiple methods of assessment are required. Methods: There are 35 courses included in the MBBS program in the college of medicine, KKU. these are taught over five years in addition to a preparatory year and the internship year. the curriculum can still be described as discipline based. a survey was planned to study the current assessment situation. this is a cross-sectional descriptive study. the data collection methods used were survey and study of the documents of the courses. an online questionnaire was developed. the responses were analyzed using descriptive statistics to determine frequencies, averages and percentages. the study was conducted during the period January-May 2014. Results: Twenty course coordinators responded to the survey (57%). Eleven of the courses covered were basic and nine were clinical. Multiple tests as well as multiple methods of continuous assessment were used in the courses studied. Some of the methods used for summative assessment are no longer recommended in current assessment practices in medical education. Real OSCE was used only in one clinical course. Standard setting methods were not used and a fixed pass mark was used instead. Conclusions: Important shortcomings in student assessment system in many of the courses studied were identified. Less educationally desirable assessment methods and practices are still used in some courses such as unattended single long case examination. More attention should be given to technical aspects of assessment.